2010
DOI: 10.4314/as.v9i1.57456
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dependence of some physical properties of a typic plithaqaualf on the basement complex in southwestern Nigeria

Abstract: Knowledge of soil physical and chemical properties is a key to making agronomic and environmental decisions. The objective of this study was to assess the extent of spatial dependence and spatial structure of some soil physical properties and implications on pedogenesis and management in the basement complex soils of southwestern Nigeria. Surface soil (0-15cm) samples were collected at 10 m 2 rigid grid intervals in a 0.5 hectare plot under fallow along Parry road in University of Ibadan. Classical statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Knowledge of soil properties is the key in making agronomic and environmental decisions (Obi et al ., 2010). Variability in soil properties has been observed due to various anthropogenic management practices and the soil-forming factor.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of soil properties is the key in making agronomic and environmental decisions (Obi et al ., 2010). Variability in soil properties has been observed due to various anthropogenic management practices and the soil-forming factor.…”
Section: Resultsmentioning
confidence: 99%
“…High variation in the clay fractions of the soils could be due to the existence of argillic horizons in the pedons; indicating wide variation in the clay contents of the horizons and increased clay down the soil profile. Soil properties manifest both long and short range variability and are multivariate in nature (Obi et al, 2010). This variability can be studied using CV in which case, ranking of CV of soil properties are grouped into different classes including least (< 15%), moderately (15 < 35%) and highly (> 35%) variable according to Wilding (1985).…”
Section: Physical Properties Of Soilsmentioning
confidence: 99%
“…The nugget semivariance expressed as a percentage of the total semivariance enables comparison of the relative size of the nugget effect among soil properties (Trangmar et al 1985). Several studies (Iqbal et al 2005;Duffera et al 2007;Santra et al 2008;Souza et al 2009, Obi and Nnadi, 2010, Obi et al, 2010a have shown that components of soil texture are strongly spatially dependent. Thus, influencing other soil properties (physical, chemical or biological) that may equally display strong spatial dependence.…”
Section: Introductionmentioning
confidence: 99%